HISTORY AND PERSPECTIVES OF CONTEMPORARY RUSSIAN CORPORATE VOLUNTEERING - Troska, Zulfiya; Gorlova , Natalia; Gribkova, Olga; Kuzub, Ekaterina; Starovojtova, Larisa (Revista Inclusiones, 2020)
The article is devoted to the history of corporate volunteering formation. Simultaneously, it describes the basic features of modern Russian corporate volunteering and its development prospects. The paper presents practical guidelines aimed at enhancing the involvement of personnel in socially significant activities, which improves the quality of working with them. These models are comprehensive and universal. The practical significance of the study lies in the fact that its conclusions and recommendations can be used in organizing voluntary activity in Russian companies and in the successful implementation of volunteer projects and programs.